2005
DOI: 10.1086/428587
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐DeficientDrosophilaFlies as a Fast, High‐Throughput Model for the Study of Antifungal Drug Efficacy against Invasive Aspergillosis andAspergillusVirulence

Abstract: Invasive aspergillosis (IA) is the most important opportunistic mycosis in immunosuppressed patients. The lack of a sufficient number of effective antifungals and our incomplete understanding of the pathogenesis of IA contribute to its overall unfavorable prognosis. Studies of drug efficacy against IA and Aspergillus virulence rely on conventional animal models that are laborious and use limited numbers of animals; alternative, less cumbersome in vivo models are desirable. Using different inoculation models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 24 publications
0
91
1
10
Order By: Relevance
“…47 Therefore, because flies are infected and maintained at 29°C, certain aspects of fungal virulence in mammals may not be accurately modeled in this organism; Galleria, which can be maintained at 37°C, the mammalian physiologic temperature, may be used instead, taking into account however that increasing the temperature of Galleria to 37°C itself alters cellular and humoral immune responses. 48,49 Second, the alb1-deficient Aspergillus fumigatus mutant, which is hypovirulent in mice and flies, 11,50 was hypervirulent in Galleria, in which it appears to trigger dysregulated immunopathology. 51 Thus, the absence of virulence of a fungal strain in one host does not preclude its pathogenicity in another pathosystem.…”
Section: Fungal Virulence Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Therefore, because flies are infected and maintained at 29°C, certain aspects of fungal virulence in mammals may not be accurately modeled in this organism; Galleria, which can be maintained at 37°C, the mammalian physiologic temperature, may be used instead, taking into account however that increasing the temperature of Galleria to 37°C itself alters cellular and humoral immune responses. 48,49 Second, the alb1-deficient Aspergillus fumigatus mutant, which is hypovirulent in mice and flies, 11,50 was hypervirulent in Galleria, in which it appears to trigger dysregulated immunopathology. 51 Thus, the absence of virulence of a fungal strain in one host does not preclude its pathogenicity in another pathosystem.…”
Section: Fungal Virulence Studiesmentioning
confidence: 99%
“…11,14,15,17,19,20,43 These studies have revealed significant concordance in fungal + denotes that the corresponding non-vertebrate host has been used for studying the specific fungal pathogen. References are noted within the bracket.…”
mentioning
confidence: 96%
“…Como una alternativa para inducir la formación del grano se utilizó la larva de la polilla de la cera Galleria mellonella; los granos producidos en esta larva semejan los encontrados en humanos y mamíferos, y este modelo de infección podría utilizarse para el estudio de la formación del grano y las respuestas terapéuticas a los agentes antifúngicos en la infección por M. mycetomatis 3 . Por último, otros hongos descritos en eumicetomas, como especies de Aspergillus, Scedosporium y Fusarium, también reconocidos como agentes causantes de infecciones oportunistas, se estudiaron utilizando Drosophila melanogaster como hospedero y se encontró que el tratamiento con voriconazol protege a las moscas de la infección, a excepción de las infectadas por Scedosporium prolificans, que no mostraron mejoría 71,72 .…”
Section: Modelos Experimentalesunclassified
“…However, it is clear from this study that Drosophila can still be used for studying the effects of the anthrax toxins. Drosophila has been restricted so far in infection studies by a small number of other pathogenic organisms, such as Vibrio cholerae, Staphylococcus aureus (10), and Pseudomonas aeruginosa (11), or fungi such as Aspergillus fumigatus (12) and Cryptococcus neoformans (13). In fact, most of them rely on infection of the host by inoculation or ingestion of living bacteria or fungi.…”
Section: The Use Of Toxins In Drosophilamentioning
confidence: 99%
“…In the past, genetic analysis and pharmacological research have been combined in Drosophila successfully. For example, the efficacy of antifungal drugs against Aspergillus virulence has been tested (12), anticonvulsants have been used to dissect aspects of seizure behavior in fly models of epilepsy (20), and new peptides have been tested in fly models of Huntington's disease (21).…”
Section: The Use Of Toxins In Drosophilamentioning
confidence: 99%